Strengthening People Engagement in Aerospace Component Manufacturing: A Qualitative Study of Culture, DE&I, and Employee Participation - Haryanto, Candra; Ghazali, Ahmad (PT. EQUATOR SINAR AKADEMIA, 2026)
Implemented at a manufacturing site, culture-building initiatives such as a Culture Council, Women Forum events, and Diversity, Equity, and Inclusion (DE&I) programs were studied to determine their impact on employee engagement and organizational results. The purpose of this study is to get a better understanding of how these integrated activities affect the views, experiences, and overall work environment of employees. With the use of internal engagement indicators to bolster triangulation, a qualitative case study technique was used, which included conducting semi-structured interviews with individuals who were purposefully chosen. In order to extract meaningful patterns from the interview data, reflexive thematic analysis was used. Thirdly, a more positive organizational climate, indicated by high favorable engagement scores, was a cumulative effect of the three main findings: first, culture-building initiatives considerably increased employee voice and cross-functional participation; second, DE&I and Women Forum programs improved perceptions of inclusion and belonging; and third, these improvements individually contributed to the better climate. Employee experience, psychological safety, and organizational attitudes may all be greatly improved by cultural interventions that are participatory and inclusion-driven, according to the study's findings. These results show how valuable it is to combine inclusive practices with continuous listening methods, and they provide useful insights for firms that want to increase participation via integrated cultural initiatives. To learn more about how cultural initiatives work in different types of organizations, this study calls for further comparative and longitudinal studie.